Respuesta :
Answer:
[tex]x=\frac{5+\sqrt{15}}{2},\:x=\frac{5-\sqrt{15}}{2}[/tex]
Step-by-step explanation:
[tex]\mathrm{For\:a\:quadratic\:equation\:of\:the\:form\:}ax^2+bx+c=0\mathrm{\:the\:solutions\:are\:}[/tex]
[tex]x_{1,\:2}=\frac{-b\pm \sqrt{b^2-4ac}}{2a}[/tex]
[tex]\mathrm{For\:}\quad a=2,\:b=-10,\:c=5[/tex]
[tex]x_{1,\:2}=\frac{-\left(-10\right)\pm \sqrt{\left(-10\right)^2-4\cdot \:2\cdot \:5}}{2\cdot \:2}[/tex]
[tex]\sqrt{\left(-10\right)^2-4\cdot \:2\cdot \:5}[/tex]
Apply exponent rule: (-a)^n=a^n, if n is even
[tex]\left(-10\right)^2=10^2[/tex]
[tex]=\sqrt{10^2-4\cdot \:2\cdot \:5}[/tex]
[tex]\mathrm{Multiply\:the\:numbers:}\:4\cdot \:2\cdot \:5=40[/tex]
[tex]=\sqrt{10^2-40}[/tex]
[tex]10^2=100[/tex]
[tex]=\sqrt{100-40}[/tex]
[tex]\mathrm{Subtract\:the\:numbers:}\:100-40=60[/tex]
[tex]=\sqrt{60}[/tex]
[tex]60\:\mathrm{divides\:by}\:2\quad \:60=30\cdot \:2[/tex]
[tex]=2\cdot \:30[/tex]
[tex]30\:\mathrm{divides\:by}\:2\quad \:30=15\cdot \:2[/tex]
[tex]=2\cdot \:2\cdot \:15[/tex]
[tex]15\:\mathrm{divides\:by}\:3\quad \:15=5\cdot \:3[/tex]
[tex]=2\cdot \:2\cdot \:3\cdot \:5[/tex]
[tex]2,\:3,\:5\mathrm{\:are\:all\:prime\:numbers,\:therefore\:no\:further\:factorization\:is\:possible}[/tex]
[tex]=2\cdot \:2\cdot \:3\cdot \:5[/tex]
[tex]=2^2\cdot \:3\cdot \:5[/tex]
[tex]=\sqrt{2^2\cdot \:3\cdot \:5}[/tex]
Apply Radical Rule:
[tex]=\sqrt{2^2}\sqrt{3\cdot \:5}[/tex]
Apply Radical Rule:
[tex]\sqrt{2^2}=2[/tex]
[tex]=2\sqrt{3\cdot \:5}[/tex]
[tex]\mathrm{Refine}[/tex]
[tex]=2\sqrt{15}[/tex]
[tex]x_{1,\:2}=\frac{-\left(-10\right)\pm \:2\sqrt{15}}{2\cdot \:2}[/tex]
[tex]\mathrm{Separate\:the\:solutions}[/tex]
[tex]x_1=\frac{-\left(-10\right)+2\sqrt{15}}{2\cdot \:2},\:x_2=\frac{-\left(-10\right)-2\sqrt{15}}{2\cdot \:2}[/tex]
[tex]\frac{-\left(-10\right)+2\sqrt{15}}{2\cdot \:2}[/tex]
Apply Rule -(-a)=a
[tex]=\frac{10+2\sqrt{15}}{2\cdot \:2}[/tex]
[tex]\mathrm{Multiply\:the\:numbers:}\:2\cdot \:2=4[/tex]
[tex]=\frac{10+2\sqrt{15}}{4}[/tex]
[tex]=\frac{2\left(5+\sqrt{15}\right)}{4}[/tex]
[tex]\mathrm{Cancel\:the\:common\:factor:}\:2[/tex]
[tex]=\frac{5+\sqrt{15}}{2}[/tex]
[tex]\frac{-\left(-10\right)-2\sqrt{15}}{2\cdot \:2}[/tex]
[tex]=\frac{10-2\sqrt{15}}{2\cdot \:2}[/tex]
[tex]\mathrm{Multiply\:the\:numbers:}\:2\cdot \:2=4[/tex]
[tex]=\frac{10-2\sqrt{15}}{4}[/tex]
[tex]=\frac{2\left(5-\sqrt{15}\right)}{4}[/tex]
[tex]\mathrm{Cancel\:the\:common\:factor:}\:2[/tex]
[tex]=\frac{5-\sqrt{15}}{2}[/tex]
[tex]\mathrm{The\:solutions\:to\:the\:quadratic\:equation\:are:}[/tex]
[tex]x=\frac{5+\sqrt{15}}{2},\:x=\frac{5-\sqrt{15}}{2}[/tex]